Topological properties in the spatial distribution of amphibians in Alabama USA for the use of large scale conservation - X. Chen (Animal Biodiversity and Conservation, 2008)
Large-scale biodiversity conservation is urgently needed due to increasing habitat loss and fragmentation. Understanding topological perspectives of species' distribution patterns can provide useful information for linking conservation studies at larger scales. We studied topological properties of localities in Alabama where 60 species of 12 families of amphibians were present. Analysis included a clustering coefficient which measures the strength of a population group, the relationship between occurrence localities and species number, the fractal dimension of occurrence localities (which emphasizes spatial irregularity), and distance to nearest-neighbor. The results indicate that the clustering coefficients of most amphibian species were low, but were higher for species with few occurrence localities, such as Rana sylvatica and Limnaoedus ocularis. The general relationship between species number and occurrence localities was that the majority of species held few localities in their distribution, while the remaining species occupied a greater number of localities. The fractal dimension (FD) for all amphibian localities was about 1.58, although FD was low for most individual species. We identified four relationships in the distribution of distance to nearest-neighbor: linear, logarithmic, power and polynomial. These topological properties may indicate intrinsic features about amphibians in Alabama and provide useful information for regional planning. Enhancing landscape linkages across a large area using undisturbed areas, such as 300-500 km in diameter may be a good approach to conservation practice in this region. Steps needed for biodiversity conservation planning in Alabama include creating or conserving small habitats across agricultural and urban land, and maintaining suitable spatial complexity and distance to nearest neighbors.